Gender Differences in the Psychosocial Functioning of Parents During the COVID-19 Pandemic - O’Sullivan, Katriona; Rock, Nicole; Burke, Lydia; Boyle, Neasa; Joksimovic, Natasha; Foley, Holly; Clark, Serena (Frontiers in Psychology, 2022)
The COVID-19 pandemic significantly affected family life, increasing parental stress around health, job losses, reduced salaries, and maintaining domestic life in lockdown and social isolation. The transition to home-schooling and remote work with school and workplace closures caused additional stressors as families began living, working, and educating in one place. This research aims to understand the relationship between the pandemic and parental stress, focusing on family well-being and established characteristics of the family unit that may cause some family members to experience the adverse consequences of the pandemic in more or less profound ways, especially mothers. Previous research shows that mothers carry more family responsibilities than fathers and can experience higher stress levels. This study employed a quantitative cross-sectional online survey to extend our understanding of the interaction between home-schooling, work and home life, and stress levels in a group of 364 parents. In total, 232 mothers and 132 fathers completed the survey. Results revealed mothers were 10 times more likely to be responsible for home-schooling than fathers, and 44% of mothers felt they had no help with home-schooling and were generally more stressed than fathers. These results show that lack of support, managing home-schooling, and being a mother predicted increased stress. 10% of mothers reported leaving their jobs due to pressure added by home-schooling. This study broadens the understanding of the pandemic’s impact on gender imbalances in family responsibilities. It emphasises the need for extra consideration for the impact on mothers as we emerge from this pandemic.